Estudo teórico das propriedades ópticas dos BaWO4 e PbWO4 - Ferreira, Márcio Douvel (2012)
Among the scheelites, we highlight the Barium Tungstats (BaWO4) and lead tungstate (PbWO4). These compounds can be synthesized by various synthetic routes. However, we can highlight the hydrothermal synthesis method assisted by microwave (SHM). Using this technique, one can use various solvents, surfactants and different synthesis conditions, such as time and temperature. Thus, crystals can be synthesized with morphologies with growth plans defined. The PbWO4 and BaWO4 powders were synthesized by SHM and characterized by techniques: XRD, Raman spectroscopy (FT-Raman), UV-Vis, photoluminescence and FEG-SEM. Theoretical models have been proposed based on the lattice parameters (a=b < c) and the cartesian coordinates (x, y, z) obtained by the Rietveld refinement performed for the powders. We proposed a theoretical model, crystalline, highly organized for each compound and two theoretical models disordered: the model with the shift modifier network at 0.5 Å in the Z direction and the third model the displacement of W-forming network, at 0.5 Å in the directions (x, y, x) in relation to oxygen. The calculations were performed using the DFT method, B3LYP functional. Models showed 13 crystalline Raman active modes, according to the calculations of group theory. The frequencies calculated theoretically for BaWO4 and PbWO4 are in accordance with experimental data. The models presented displaced Egap lower compared to model crystalline defects due to the simulated unit cell. The theoretical data show that the photoluminescence emission is directly related to structural disorder.